Crosslinkable and Chelatable Organic Ligand Enables Interfaces and Grains Collaborative Passivation for Efficient and Stable Perovskite Solar Cells. Issue 22 (2nd May 2022) - Ma, Zongwen; Yu, Runnan; Xu, Zhiyang; Wu, Guangzheng; Gao, Huaizhi; Wang, Ruyue; Gong, Yongshuai; Yang, Jing; Tan, Zhan'ao
Abstract: The organic–inorganic halide perovskite solar cell (PerSC) is the state‐of‐the‐art emerging photovoltaic technology. However, the environmental water/moisture and temperature‐induced intrinsic degradation and phase transition of perovskite greatly retard the commercialization process. Herein, a dual‐functional organic ligand, 4, 7‐bis((4‐vinylbenzyl)oxy)‐1, 10‐phenanthroline (namely, C1), with crosslinkable styrene side‐chains and chelatable phenanthroline backbone, synthesized via a cost‐effective Williamson reaction, is introduced for collaborative electrode interface and perovskite grain boundaries (GBs) engineering. C1 can chemically chelate with Sn 4+ in the SnO2 electron transport layer and Pb 2+ in the perovskite layer via coordination bonds, suppressing nonradiative recombination caused by traps/defects existing at the interface and GBs. Meanwhile, C1 enables in situ crosslinking via thermal‐initiated polymerization to form a hydrophobic and stable polymer network, freezing perovskite morphology, and resisting moisture degradation. Consequently, through collaborative interface‐grain engineering, the resulting PerSCs demonstrate high power conversion efficiency of 24.31% with excellent water/moisture and thermal stability. The findings provide new insights of collaborative interface‐grain engineering via a crosslinkable and chelatable organic ligand for achieving efficient and stable PerSCs. Abstract : A dual‐function of crosslinking and chelating strategy is established to dramatically eliminate the defects and enhance the long‐term stability of perovskite solar cells (PerSCs) via a crosslinkable organic ligand (C1). Though chemical anchoring and in situ crosslinking of C1, electrode interfaces, and perovskite grains are collaboratively optimized, resulting in highly efficient and stable PerSCs.